An Overview of the Development of Nursing Education as University Education in Nepal - Koirala, Manisa (Pragya Darshan प्रज्ञा दर्शन, 2023)
Nursing is a practice based discipline or noble profession includes the prevention & protection of illness or injury, care of disease, promotion and optimization of health & abilities, alleviation and rehabilitation from suffering including advocacy in the care of individuals, families, communities, and populations. This review article intended to assess the development of nursing education in Nepal. Total 50 related article or literature were reviewed through searching electronic database specially in Pub Med, Research gate, Google Scholar, Google etc. and save the data by creating the library via Zoster software. The more relevant articles were selected, critically analyzed, cited them appropriately and also added in reference. During the reviewed of the article it was found that the Nursing education was formally started in Nepal 2013 BS from Proficiency Certificate Level (PCL) of Nursing with the initiation of government. With the different developmental phases, it was upgraded from ANM, PCL, Bachelor (PBBN, BN, BNS, B.Sc. Nursing, BMS), Master nursing including PhD in Nursing till 2068 BS in Nepal. Initially started from government level than move to Tribhuvan University since 1972AD, nevertheless more than 6 Universities including CTEVT were involved to produce different level Nursing human resource in Nepal presently.